(untitled) (Research, Society and Development, 2023)
The purpose of this experience report is to portray the experience lived during the activities carried out in the Samuzinho Project. This is a descriptive study, of the Experience Report type, built from an initiative of the Nucleus of Education in Urgency (NEU) of the Mobile Emergency Care Service (SAMU 192) of Teresina - PI. The activities were developed with children from 7 to 12 years old, from public and private schools, from September 2018 to August 2019, under the guidance of SAMU 192 instructors from Teresina, Piauí. The children were certified as junior rescuers, through training in first aid with qualification to act in emergency situations until professional rescuers arrive at the scene, also making them multipliers of knowledge and citizenship. This activity contributed to the construction and improvement of the know-how of SAMU Teresina professionals, greatly enriching the service and citizenship education of the participants. Among the final considerations, it is recognized that the Samuzinho Project was successful in all its editions and contributed significantly to the psychosocial development process of the participating children. In addition, implementing and maintaining permanent education processes in emergencies with the SAMU is of fundamental importance for the qualification of the service.